Individualized nutritional intervention improves the nutritional status of liver cancer patients after transcatheter arterial chemoembolization - Sun, Qian; Yu, Huixi; You, Tao; Zhang, Dong (Nutrición hospitalaria : organo oficial de la Sociedad Española de Nutrición Parenteral y Enteral, 2024)
Introduction: to explore the effect of individualized nutritional intervention on the nutritional status of patients with liver cancer after transcatheter arterial chemoembolization (TACE). Methods: 56 patients who underwent TACE in our hospital from March 2022 to March 2023 were selected as the study subjects. The patients were randomly divided into a control group (28 cases) and an intervention group (28 cases). The control group received routine dietary intervention, while the intervention group received individualized nutritional intervention. We analyzed the body mass index (BMI), nutritional risk screening 2002 (NRS 2002), nutritional status, liver function status, and incidence of complications in two groups of patients before TACE, 3 days after TACE, and 1 month after TACE. Results: on the third day after TACE, the nutritional related indicators of both groups of patients showed a significantly decrease compared to those before TACE (p < 0.05), while the majority of liver function indicators significantly increased (p < 0.05). Compared with those at 3 days after TACE, the nutritional status of the intervention group patients significantly improved (p < 0.05) and liver function indicators significantly decreased (p < 0.05) 1 month after TACE. One month after TACE, all nutritional indicators in the intervention group were significantly higher than those in the control group (p < 0.05), and AST was significantly lower than that in the control group (p < 0.05). The incidence of gastrointestinal complications and electrolyte disorders in the intervention group were significantly lower than that in the control group (p < 0.05). Conclusion Individualized nutritional intervention can effectively improve nutritional status, improve liver function, and reduce the incidence of postoperative complications in liver cancer patients after TACE. It was worth promoting.